Single Stranded Fully Modified-Phosphorothioate Oligonucleotides can Induce Structured Nuclear Inclusions, Alter Nuclear Protein Localization and Disturb the Transcriptome In Vitro - Flynn, Loren L.; Li, Ruohan; Pitout, Ianthe L.; Aung-Htut, May T.; Larcher, Leon M.; Cooper, Jack A. L.; Greer, Kane L.; Hubbard, Alysia; Griffiths, Lisa; Bond, Charles S.; Wilton, Steve D.; Fox, Archa H.; et al. (Frontiers in Genetics, 2022)
Oligonucleotides and nucleic acid analogues that alter gene expression are now showing therapeutic promise in human disease. Whilst the modification of synthetic nucleic acids to protect against nuclease degradation and to influence drug function is common practice, such modifications may also confer unexpected physicochemical and biological properties. Gapmer mixed-modified and DNA oligonucleotides on a phosphorothioate backbone can bind non-specifically to intracellular proteins to form a variety of toxic inclusions, driven by the phosphorothioate linkages, but also influenced by the oligonucleotide sequence. Recently, the non-antisense or other off-target effects of 2′ O- fully modified phosphorothioate linkage oligonucleotides are becoming better understood. Here, we report chemistry-specific effects of oligonucleotides composed of modified or unmodified bases, with phosphorothioate linkages, on subnuclear organelles and show altered distribution of nuclear proteins, the appearance of highly stable and strikingly structured nuclear inclusions, and disturbed RNA processing in primary human fibroblasts and other cultured cells. Phosphodiester, phosphorodiamidate morpholino oligomers, and annealed complimentary phosphorothioate oligomer duplexes elicited no such consequences. Disruption of subnuclear structures and proteins elicit severe phenotypic disturbances, revealed by transcriptomic analysis of transfected fibroblasts exhibiting such disruption. Our data add to the growing body of evidence of off-target effects of some phosphorothioate nucleic acid drugs in primary cells and suggest alternative approaches to mitigate these effects.